Paracrine Engineering of Human Explant‐Derived Cardiac Stem Cells to Over‐Express Stromal‐Cell Derived Factor 1α Enhances Myocardial Repair. (21st April 2016) - Tilokee, Everad L.; Latham, Nicholas; Jackson, Robyn; Mayfield, Audrey E.; Ye, Bin; Mount, Seth; Lam, Buu‐Khanh; Suuronen, Erik J.; Ruel, Marc; Stewart, Duncan J.; Davis, Darryl R.
Abstract : First generation cardiac stem cell products provide indirect cardiac repair but variably produce key cardioprotective cytokines, such as stromal‐cell derived factor 1α, which opens the prospect of maximizing up‐front paracrine‐mediated repair. The mesenchymal subpopulation within explant derived human cardiac stem cells underwent lentiviral mediated gene transfer of stromal‐cell derived factor 1α. Unlike previous unsuccessful attempts to increase efficacy by boosting the paracrine signature of cardiac stem cells, cytokine profiling revealed that stromal‐cell derived factor 1α over‐expression prevented lv‐mediated "loss of cytokines" through autocrine stimulation of CXCR4+ cardiac stem cells. Stromal‐cell derived factor 1α enhanced angiogenesis and stem cell recruitment while priming cardiac stem cells to readily adopt a cardiac identity. As compared to injection with unmodified cardiac stem cells, transplant of stromal‐cell derived factor 1α enhanced cells into immunodeficient mice improved myocardial function and angiogenesis while reducing scarring. Increases in myocardial stromal‐cell derived factor 1α content paralleled reductions in myocyte apoptosis but did not influence long‐term engraftment or the fate of transplanted cells. Transplantation of stromal‐cell derived factor 1α transduced cardiac stem cells increased the generation of new myocytes, recruitment of bone marrow cells, new myocyte/vessel formation and the salvage of reversibly damaged myocardium to enhance cardiac repair after experimental infarction. Stem Cells 2016;34:1826–1835